Early Life Stress and the Onset of Obesity: Proof of MicroRNAs’ Involvement Through Modulation of Serotonin and Dopamine Systems’ Homeostasis - Tavares, Gabriel Araujo; Torres, Amada; de Souza, Julliet Araujo (Frontiers in Physiology, 2020)
Healthy persons hold a very complex system for controlling energy homeostasis. The system functions on the interconnected way between the nutritional, endocrine, neural, and epigenetic regulation, which includes the microRNAs (miRNAs). Currently, it is well accepted that experiences of early life stress (ELS) carriages modification of the central control of feeding behavior, one of the factors controlling energy homeostasis. Recently, studies give us a clue on the modulation of eating behavior, which is one of the main factors associated with the development of obesity. This clue connected the neural control though the serotonin (5HT) and dopamine (DA) systems with the fine regulation of miRNAs. The first pieces of evidence highlight the presence of the miR-16 in the regulation of the serotonin transporter (SERT) as well as the receptors 1a (5HT1A) and 2a (5HT2A). On the other hand, miR-504 is related to the dopamine receptor D2 (DRD2). As our knowledge advance, we expected to discover other important pathways for the regulation of the energy homeostasis. As both neurotransmission systems and miRNAs seem to be sensible to ELS, the aim of this review is to bring new insight about the involvement of miRNAs with a central role in the control of eating behavior focusing on the influences of ELS and regulation of neurotransmission systems.